Changes in relative and absolute concentrations of plasma phospholipid fatty acids observed in a randomized trial of Omega-3 fatty acids supplementation in Uganda. (November 2016) - Song, Xiaoling; Diep, Pho; Schenk, Jeannette M.; Casper, Corey; Orem, Jackson; Makhoul, Zeina; Lampe, Johanna W.; Neuhouser, Marian L.
Abstract: Expressing circulating phospholipid fatty acids (PLFAs) in relative concentrations has some limitations: the total of all fatty acids are summed to 100%; therefore, the values of individual fatty acid are not independent. In this study we examined if both relative and absolute metrics could effectively measure changes in circulating PLFA concentrations in an intervention trial. 66 HIV and HHV8 infected patients in Uganda were randomized to take 3 g/d of either long-chain omega-3 fatty acids (1856 mg EPA and 1232 mg DHA) or high—oleic safflower oil in a 12-week double-blind trial. Plasma samples were collected at baseline and end of trial. Relative weight percentage and absolute concentrations of 41 plasma PLFAs were measured using gas chromatography. Total cholesterol was also measured. Intervention-effect changes in concentrations were calculated as differences between end of 12-week trial and baseline. Pearson correlations of relative and absolute concentration changes in individual PLFAs were high (>0.6) for 37 of the 41 PLFAs analyzed. In the intervention arm, 17 PLFAs changed significantly in relative concentration and 16 in absolute concentration, 15 of which were identical. Absolute concentration of total PLFAs decreased 95.1 mg/L (95% CI: 26.0, 164.2; P =0.0085), but total cholesterol did not change significantly in the intervention arm. No significant change was observed in any of the measurements in the placebo arm. Both relative weight percentage and absolute concentrations could effectively measure changes in plasma PLFA concentrations. EPA and DHA supplementation changes the concentrations of multiple plasma PLFAs besides EPA and DHA.Both relative weight percentage and absolute concentrations could effectively measure changes in plasma phospholipid fatty acid (PLFA) concentrations. Highlights: Both relative weight percentage and absolute concentrations could effectively measure changes in plasma phospholipid fatty acid (PLFA) concentrations. EPA and DHA supplementation changed the concentrations of multiple plasma PLFAs besides EPA and DHA. EPA and DHA supplementation did not change plasma total cholesterol concentration, but decreased the concentration of total PLFAs analyzed.